Efficient Photocatalytic Degradation of CI Reactive Red 195 Using UV-C/ZnO Heterogeneous System: Process Optimization and Degradation Kinetics - Ozkan, Betul Cicek; Selen, Veyis; Dursun, Gulbeyi (Wiley-V C H Verlag Gmbh, 2026)
This study investigates the photocatalytic degradation of CI Reactive Red 195 (RR195) using a UV-C/ZnO slurry annular photoreactor. Key parameters-ZnO loading (0-5.0 g L- 1), dye concentration (150-550 mg L- 1), aeration (0-1.0 L min- 1), and temperature (283-323 K)-were examined at natural pH (similar to 5.6). Degradation improved with higher catalyst loading, aeration, and temperature, but decreased at higher dye concentrations due to light attenuation and competition effects. Under optimal conditions (4.0 g L- 1 ZnO, 0.5 L min- 1 aeration, 293 K), complete decolorization of 150 mg L- 1 RR195 occurred within 30 min. The process followed pseudo-first-order kinetics with a low activation energy (12.18 kJ mol- 1), indicating efficiency under mild conditions. LC-MS/MS and FTIR analyses confirmed a stepwise mechanism involving azo bond cleavage and subsequent oxidative mineralization. Overall, the UV-C/ZnO system proves to be an effective method for treating dye-contaminated wastewater.
Keywords: CI Reactive Red 195; degradation kinetics; LC-MS/MS; photocatalysis; UV-C irradiation; ZnO photocatalyst